Role of Sociocultural Factors in Depression among Elderly of Twin Cities (Rawalpindi and Islamabad) of Pakistan - Javed, Saira (Hindawi Publishing Corporation, 2014)
This research was conducted to examine the role of sociocultural factors on depression among elderly of twin cities (Rawalpindi and Islamabad) of Pakistan. 310 older adults participated in the present study. Through convenient sampling technique, face to face interview was carried out for data collection. Urdu translated Geriatric Depression Scale Short Form and demographic sheet were used to test hypotheses. Descriptive statistics and t-test were used for data analysis. Results showed significant mean differences among gender, marital status, family system, and status of employment on depression. Financial crisis, feeling of dejection because of isolation, and trend of nuclear family system have been observed as strong predictors of depression in older adults.